DEALING WITH TOPOLOGICAL RELATIONS IN UNDERGROUND NETWORKS - M. Lacroix (InterCarto. InterGIS, 2015)
Ten years ago, 25 people died and more than 150 were seriously injured in Ghislenghien (Belgium) because of construction damage to a high pressure gas pipeline. Urban networks are invisible because usually buried between 1 and 1.5 meter underground. They should be identified to prevent such accidents which involve workers and public as well. Rural and urban districts, networks concessionary and contractors; everyone could benefit from their networks becoming safer. To develop software which evaluates the risks in managing both uncertainties and topology is the focus of attention. That’s the reason why we firstly propose to determine the topological relationships between networks; secondly we propose to compute the risks taking into account the various uncertainties such as the security radius or the coordinates accuracy, before giving the different required standards for an artificial intelligence tool in order to obtain high security level.